2003
DOI: 10.1149/1.1591762
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence Properties of Eu[sup 3+]-Activated Y[sub 2]GeO[sub 5] Phosphors

Abstract: The luminescence and energy transfer properties of Eu 3ϩ in Y 2 GeO 5 have been investigated. The critical concentration at which the concentration quenching occurred under UV excitation were x ϭ 0.4 in (Y 1Ϫx Eu x ) 2 GeO 5 . To investigate the distinction of photoluminescence behavior of two transitions ͑i.e., 5 D 0 → 7 F 1 and 5 D 0 → 7 F 2 transition͒ for the Eu 3ϩ ion, the decay curves for both 5 D 0 → 7 F 1 and 5 D 0 → 7 F 2 transition have been analyzed. Furthermore the energy migration process of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
2
2
0
Order By: Relevance
“…The value is $3.0 for both of the samples (there may be some uncertainty in this value for the orthorhombic phase because of severe overlapping of the peaks attributable to the 5 D 0 / 7 F 2 and 5 D 0 / 7 F 1 transitions). The emission spectrum obtained for the monoclinic sample in the present study is comparable to that observed by Park et al, 11 for 0.007 mol% Eu 3+ doped monoclinic Y 2 GeO 5 . It is worth noting that the intensity of the electric dipole transition, 5 D 0 / 7 F 4 , is signicantly higher for the orthorhombic phase compared to the monoclinic phase, suggesting a higher electric dipole transition probability in the orthorhombic phase.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The value is $3.0 for both of the samples (there may be some uncertainty in this value for the orthorhombic phase because of severe overlapping of the peaks attributable to the 5 D 0 / 7 F 2 and 5 D 0 / 7 F 1 transitions). The emission spectrum obtained for the monoclinic sample in the present study is comparable to that observed by Park et al, 11 for 0.007 mol% Eu 3+ doped monoclinic Y 2 GeO 5 . It is worth noting that the intensity of the electric dipole transition, 5 D 0 / 7 F 4 , is signicantly higher for the orthorhombic phase compared to the monoclinic phase, suggesting a higher electric dipole transition probability in the orthorhombic phase.…”
Section: Resultssupporting
confidence: 91%
“…The former is attributed to Eu 3+ ions in the bulk, while the latter is assigned to Eu 3+ ions present in the grain boundaries of the particles. The decay proles and lifetime values for the monoclinic sample are similar to those reported by Park et al 11 The sample heated at 1400 C (monoclinic form) has a higher extent of grain boundaries in comparison to the sample heated at 900 C. At the grain boundaries, the environment around the Eu 3+ ions is highly distorted leading to poor luminescence and an associated decrease in the lifetime values. Interestingly, the 5 D 0 lifetime value is higher (almost double) for the orthorhombic phase compared to the monoclinic form.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The Eu ion is well-known for its “europium red” luminescence at approximately 613 nm based on the 4f energy levels. A series of compounds activated by Eu ion have been studied for practical application as phosphors and materials. , The interaction between the Eu ion and carbon cages might influence the spectrum and lead to a new matrix of luminescence. If europium metallofullerenes were inserted into the nanotubes, which can be seen as a new one-dimensional host material, some promising applications might be opened compared to the conventional Eu ion in its glassy or crystalline hosts.…”
Section: Introductionmentioning
confidence: 99%